G208(P) Should we consider switching to a 24-hour course of antibiotics for asymptomatic, low-risk babies with suspected early onset neonatal sepsis. (May 2019) - Devlin, H; Narendra, D; Malley, M
Abstract : NICE guidelines recommend antibiotics for suspected early onset neonatal sepsis (EONS) be discontinued at 36 hours in asymptomatic newborns with negative blood cultures and reassuring inflammatory markers. Despite this national practice remains varied with five units stopping antibiotics at 24 hours. We assessed whether two negative CRP results (<10 mg/L) and a negative culture at 24 hours would have changed the management of any babies at our level 1 neonatal unit. We retrospectively identified newborns who were screened and treated for suspected EONS over an 8 month period, noting their CRP measurements at 0 and 18–24 hours and blood culture results. Over 8 months, 463 newborns were screened for suspected EONS. There were 16 positive blood cultures (3.5%). Of these, 6 (1.3% overall) grew group-B streptococcus (GBS) within the first 24 hours and all had raised CRPs≥10 mg/L at 18–24 hours (average 57 mg/L, range 40.3–60.2 mg/L). Of the remaining positive blood cultures, 9 were contaminants and one grew a bacillus species which was reported as a likely contaminant although the baby received a 5 day course of antibiotics to cover for possible listeria infection. Of the 303 babies with two negative CRPs, no blood cultures were positive for pathogenic bacteria. Within this group there were 7 grew contaminant blood cultures including the one bacillus species. This baby was symptomatic and would not have met the criteria to stop antibiotics at 24 hours in any case. Of the 16 positive cultures, 15 were reported positive under 24 hours of incubation. The baby with the remaining culture had a raised CRP and would have been treated for 5 days irrespectively. This culture grew a contaminant. We found there were no pathogenic blood cultures among patients with two negative CRP results. The sensitivity of a CRP >10 mg/L for identifying confirmed pathological cultures was 100% in our cohort, with the negative predictive value of two CRP <10 mg/L also 100%. Retrospectively, we found that if we had reviewed the decision to stop antibiotics at 24 hours it would not have changed our decision-making based on a combination of clinical condition, CRP trend and blood culture results for all 463 babies. A clinical argument can be made for identifying a low-risk cohort of babies to stop antibiotics at 24 hours in the absence of adverse clinical or biochemical signs. Joining the five UK units already subject to this policy may provide several clinical benefits but would need careful safeguards to ensure patient safety.